21. Let i 1 be the current in R 1 and take it to be positive if it is to the right. Let i 2 be the current in R 2 and take it to be positive if it is upward. When the loop rule is applied to the lower loop, the result is E 2 − i 1 R 1 =0 . and when it is applied to the upper loop, the result is E 1 −E 2 −E 3 − i 2 R 2 =0 . The Frst equation yields i 1 = E 2 R 1 = 5 . 0V 100 Ω =0 . 050 A . The second yields
This is the end of the preview. Sign up
access the rest of the document.
This note was uploaded on 11/12/2011 for the course PHYS 2001 taught by Professor Sprunger during the Fall '08 term at LSU.